NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIAHow to use sirolimus in order to increase survival in heart transplant recipients? - Zakliczyński, Michał; Pyka, Łukasz; Trybunia, Dominika; Nożyński, Jerzy; Przybylski, Roman; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Aim : Aim of the study was to was to assess the impact of sirolimus used as part of immunosuppressive therapy on survival of orthotopic heart transplantation (OHT) recipients. Material and methods: We performed a retrospective case-control study involving all 60 OHT recipients receiving sirolimus (study group), and 60 matched individuals treated without sirolimus (control group). In almost half of the study group sirolimus was used briefly, or introduced late after OHT. However, we identified 31 pts. in whom sirolimus was introduced before the 3rd year post-transplant, and continued permanently (28M/3F, 45 ±11y/o, ischaemic cardiomyopathy in 15 pts.). Sirolimus was combined with low-dose cyclosporine-A, replaced with mycophenolate mofetil 3 years post-transplant. The study subgroup was compared with its matches from the control group (28M/3F, 44 ±11y/o, ischaemic c-pathy in 17 pts.). We compared time free from all-cause death, cardiac death and non-cardiac death. Results : Average follow-up was 2138 ±1192 days in the study group and 1949 ±1221 days in the control group (2169 ±650 vs. 1872 ±987 days, respectively in substudy). Fourteen (33%) deaths occurred in the study group and 25 (42%) in the control group (p = 0.032) – 5 (16%) deaths in the study subgroup vs. 14 (45%) deaths in the control subgroup (p = 0.028). Time free from all-cause death was significantly longer both in the whole study group and the subgroup (p = 0.044 and p = 0.019, respectively). The same trend was observed for the time free from non-cardiac death (p = 0.036 and p = 0.022, respectively). Conclusion : A combination of sirolimus with low-dose cyclo-sporine-A prolongs survival in OHT recipients, decreasing probability of non-cardiac death.